Implementation of Online Learning during the Covid-19 Pandemic - Muthmainna, Nur Ramadhani; Ahyani, Nur; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2023)
Students are expected to easily and comfortably accept online learning. This paper intends to outline how online learning was implemented at SMK Negeri 1 Gelumbang throughout the covid-19 epidemic. This study employs a phenomenological research design and is qualitative in nature. Purposive sampling was the technique that was employed. Observation, documentation, and interview-based data collection methods. Utilizing the triangulation technique, the validity of the data is tested. Interactive analysis, which includes data gathering, data reduction, data presentation, and conclusion-making, was used to obtain data analysis from the outcomes of data collecting. The findings indicated that, despite a few roadblocks, the online learning program at SMK Negeri 1 Gelumbang could be regarded to be operating successfully. Teachers at SMK Negeri 1 Gelumbang have access to Wi-Fi, and students receive free quotas as supporting elements for online learning. The low level of technological proficiency, the absence of parental involvement, and the challenging accessibility to the internet were the challenges identified.